B. infantis EVC001 Is Well-Tolerated and Improves Human Milk Oligosaccharide Utilization in Preterm Infants in the Neonatal Intensive Care Unit - Bajorek, Sarah; Duar, Rebbeca M.; Corrigan, Maxwell; Matrone, Christa; Winn, Kathryn A.; Norman, Susan; Mitchell, Ryan D.; Cagney, Orla; Aksenov, Alexander A.; Melnik, Alexey V.; Kopylova, Evguenia; Perez, Jose (Frontiers in Pediatrics, 2022)
Not all infants carry specialized gut microbes, meaning they cannot digest human milk oligosaccharides and therefore do not receive complete benefits from human milk. B. infantis EVC001 is equipped to convert the full array of complex oligosaccharides into compounds usable by the infant, making it an ideal candidate to stabilize gut function and improve nutrition in preterm infants. A prospective, open-label study design was used to evaluate the tolerability of B. infantis EVC001 and its effects on the fecal microbiota in preterm infants in a Neonatal Intensive Care Unit. 30 preterm infants <1500 grams and/or <33 weeks gestation at birth were divided into two matched groups, and control infants were enrolled and discharged prior to enrolling EVC001 infants to prevent cross-colonization of B. infantis: 1) fifteen control infants received no EVC001, and 2) fifteen infants received once-daily feedings of B. infantis EVC001 (8.0 x 109 CFU) in MCT oil. Clinical information regarding medications, growth, nutrition, gastrointestinal events, diagnoses, and procedures was collected throughout admission. Infant stool samples were collected at baseline, Study Days 14 and 28, and 34-, 36-, and 38-weeks of gestation. Taxonomic composition of the fecal microbiota, functional microbiota analysis, B. infantis, and human milk oligosaccharides (HMOs) in the stool were determined or quantified using 16S rRNA gene sequencing, metagenomic sequencing, qPCR, and mass spectrometry, respectively. No adverse events or tolerability issues related to EVC001 were reported. Control infants had no detectable levels of B. infantis. EVC001 infants achieved high levels of B. infantis (mean = 9.7 Log10 CFU/µg fecal DNA) by Study Day 14, correlating with less fecal HMOs (ρ = -0.83, P < 0.0001), indicating better HMO utilization in the gut. In this study, B. infantis EVC001 was shown to be safe, well-tolerated, and efficient in colonizing the preterm infant gut and able to increase the abundance of bifidobacteria capable of metabolizing HMOs, resulting in significantly improved utilization of human milk. Trial registration number: NCT03939546 URL of registration: https://clinicaltrials.gov/ct2/show/NCT03939546